Bacteriophage-based Vaccine: A New Dawn for Vaccine Design and Development: Bacteriophage-based Vaccine for Vaccine Design and Development - Khan, Fazal Mehmood (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
The COVID-19 epidemic has strained healthcare systems, causing stress among personnel and facing significant economic and social issues. COVID-19 patients have significant symptoms, necessitating prompt treatment. It is a global urgency to develop effective vaccinations against COVID-19. Quick immunization of the whole world population against an ever-changing, extremely deadly virus is alarming, and various vaccine techniques are being researched. Bacteriophages are helpful in the treatment of multidrug-resistant bacterial infections. But, their clinical efficacy may go far beyond. One of the most significant bioproducts in medicine is thought to be vaccines. Vaccines for a variety of diseases have been made. However, certain vaccinations have disadvantages, such as high prices and immunological responses. In this regard, the use of bacteriophages has been suggested as an exciting alternative for making more inexpensive vaccines. Bacteriophage-displayed vaccines are based on the antigens being expressed on the phage surface. This tactic uses the inherent advantages of these particles, including their high stability, inexpensive production, and adjuvant capacity. Phage-displayed, phages DNA and hybrid phage-DNA vaccines are the three phage-based vaccines that are currently offered. The traditional method for finding novel barrier protection epitopes, antigens, and mimotopes is phage display. In this frame of reference, phage particles serve as a versatile, effective, and promising strategy for making vaccine delivery systems that are more effective and should be widely applied in the future. The phage-vaccine technique can potentially address the growing demand for innovative vaccinations against emerging diseases. This short communication addresses bacteriophage uses in vaccine development and discusses recent developments in bacteriophage-based vaccinations. It also focuses on and describes bacteriophages as a novel vaccine candidate for COVID-19.